Enhancing Industry-School Linkages in Vietnam's Vocational Education and Training (VET) System for the Fourth Industrial Revolution - Nguyen Thi Minh Anh (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2024)
In the context of the Fourth Industrial Revolution (4IR), enhancing the linkage between industry and the Vocational Education and Training (VET) system is a strategic imperative for Vietnam. This study aims to deeply analyze the dynamics, challenges, and success factors of these industry-school partnerships. Employing a sequential explanatory mixed-methods design, the research first conducted a quantitative survey among leaders of VET institutions and companies, which was then followed by in-depth qualitative interviews with key stakeholders to explore the statistical findings. The results reveal a significant paradox: while there is universal agreement on the importance of collaboration, current practices are predominantly superficial (e.g., guest lectures) rather than substantive (e.g., joint curriculum development). The study identifies a systemic 'trust deficit' and a 'cultural gulf' as the core barriers, rather than a mere lack of willingness. Notably, the Information Technology (IT) sector emerges as an important exception, driven by necessity to form deeper, more agile partnerships. The study concludes that effective policy should shift from simply encouraging "more collaboration" to strategically building trust and fostering an ecosystem conducive to deep partnerships, in which intermediary entities play a crucial role as "trust brokers".